THE SYSTEM OF SANCTIONS FOR THE CHILD AND ITS IMPLEMENTATION (Study of child protection in the perspective) - Muchtar, Syamsuddin (Journal of Humanity, 2014)
Â Â The judiciary and Criminal child who in fact is for the protection and welfare of children as part of social welfare, wants sanctions preferred action instead of criminal sanctions. In other words, criminal sanctions would only be used as a last effort (the last resort). But in fact, these types of criminal sanctions, in particular imprisonment sanctions are still used as a sanction